The impact of natural resources, human capital, and foreign direct investment on the ecological footprint: The case of the United States. (October 2019) - Zafar, Muhammad Wasif; Zaidi, Syed Anees Haider; Khan, Naveed R.; Mirza, Faisal Mehmood; Hou, Fujun; Kirmani, Syed Ali Ashiq
Abstract: This study explores the effect of the amounts of natural resources, human capital, and foreign direct investment on the ecological footprint in the presence of energy consumption and economic growth using US data from 1970 to 2015. We use the Zivot-Andrews unit root method to check the stationary properties of data series, along with structural breaks and employ an Auto Regressive Distributive Lag (ARDL) model to estimate the short-run and long-run elasticities among the variables. Our findings suggest that economic growth and energy consumption have negative relationships with the ecological footprint. Natural resources and human capital are helpful in curtailing ecological footprint, as is foreign direct investment (FDI). The results of Granger causality show bidirectional causality between energy consumption and the ecological footprint and between economic growth and the ecological footprint, while unidirectional causality runs from natural resources to the ecological footprint and from human capital to natural resources. The US must attract more FDI and human capital from other countries to ensure that established companies and new firms can innovate swiftly in support of the quality of life and sustainable development. Graphical abstract: This study examines the impact of natural resources, human capital, and foreign direct investment on ecological footprint in the United States.Image 1 Highlights: This study analyzes the impact of human capital, natural resources and foreign direct investment on ecological footprint. Study is done for United State of America (USA) during the period of 1970–2015. ARDL approach is used to examine the long and short-run elasticities. Human capital and natural resources abundance reduce ecological footprint. Economic growth and energy consumption increase the ecological footprint.